Foods to Avoid During Pregnancy - Isabel Valentín-Oquendo (EDIS, 2002)
This publication is FCS8752-Eng, one of a series of the Department of Family, Youth, and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002. Reviewed by Jennifer Hillan, MSH, RD, LD/N and Amy Simonne, Ph.D., University of Florida.